FORMATION OF CERTAIN SUMMATION FORMULAE BASED ON HALF ARGUMENT INVOLVING HYPERGEOMETRIC FUNCTION (Global Journal of Science Frontier Research, 2011)
The main objective of the present paper is to obtain certain new results involving Hypergeometric function.The results presented here are presumably new.
Keywords: Gaussian Hypergeometric function; Contiguous function; Recurrence relation; Bailey summation theorem and Legendre duplication formula